Relationship Between Knowledge of Mothers, Umbilical Cord Care and Umbilical Cord Infection with Length of Umbilical Cord Detachment in Newborns in Tanjung Lago Village, Banyuasin Regency In 2021 - Rencima Pakpahan; Helni Anggraini; Satra Yunola (Science Midwifery, 2022)
readkground: The length of the umbilical cord detachment is influenced by the way the umbilical cord is cared for, the humidity of the umbilical cord, the sanitary conditions of the environment around the neonate, and the incidence of infection in the umbilical cord due to actions or treatments that do not meet hygiene requirements or do not comply with predetermined standards. The impact of incorrect umbilical cord care can result in a longer umbilical cord detachment time and umbilical cord infection. Infection in the umbilical cord can cause sepsis, meningitis, and others. This study aims to determine the relationship between maternal knowledge, umbilical cord care and umbilical cord infection with the length of umbilical cord detachment in newborns. This research method is analytic observational with a cross sectional approach. The results showed that there was a relationship between mother's knowledge of the length of umbilical cord detachment with p value0.004, there was also a relationship between umbilical cord infection and length of umbilical cord detachment with ap value0.001 and there was no relationship between umbilical cord care with open or open methods. closed to the length of umbilical cord detachment with ap value0,107. The conclusion of this study is that maternal knowledge and infection in the umbilical cord can affect the length of umbilical cord detachment in newborns. Suggestions from this study all mothers should increase their knowledge about umbilical cord care and length of umbilical cord separation through social media, internet, etc., and to pay more attention to hygiene in the area around the umbilical cord in infants to prevent infection. And it is hoped that health workers can improve health promotion, especially regarding the length of the umbilical cord detachment in newborns.